2008
DOI: 10.1021/bc800280u
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial and Antifouling Polymer Brushes Incorporating Antimicrobial Peptide

Abstract: Surface-initiated atom transfer radical polymerization (ATRP) has been used to prepare antifouling copolymer brushes based on 2-(2-methoxyethoxy)ethyl methacrylate (MEO(2)MA) and hydroxyl-terminated oligo(ethylene glycol) methacrylate (HOEGMA). The amount of hydroxyl reactive groups incorporated into the brushes was varied by changing the composition of the monomer mixture. These coatings were subsequently functionalized by a natural antibacterial peptide, magainin I, via an oriented chemical grafting on hydro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
230
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 239 publications
(240 citation statements)
references
References 52 publications
8
230
0
1
Order By: Relevance
“…In order to avoid implant-associated infections, several strategies have been reported with the aim of creating antimicrobial surfaces, such as the development of (i) non-fouling surfaces (surfaces that avoid protein adsorption and cell adhesion) [1,[18][19][20], (ii) surfaces previously colonized with non-pathogenic bacteria [9], (iii) surfaces combined with biocidal substances [21][22][23] and (iv) surfaces combined with antibiotics [24][25][26].…”
Section: Antimicrobial Coatingsmentioning
confidence: 99%
See 4 more Smart Citations
“…In order to avoid implant-associated infections, several strategies have been reported with the aim of creating antimicrobial surfaces, such as the development of (i) non-fouling surfaces (surfaces that avoid protein adsorption and cell adhesion) [1,[18][19][20], (ii) surfaces previously colonized with non-pathogenic bacteria [9], (iii) surfaces combined with biocidal substances [21][22][23] and (iv) surfaces combined with antibiotics [24][25][26].…”
Section: Antimicrobial Coatingsmentioning
confidence: 99%
“…Humblot et al [68] reported that the immobilized AMPs had a bacteriostatic rather that bactericidal effect, perhaps due to the low peptide concentration or short contact time. Other research has performed the immobilization through long linkers in an attempt to permit sufficient flexibility to penetrate target cell membranes [1,69,70], as the directly attached AMPs lost their antimicrobial activity. Hilpert et al [71], in their screening and characterization of surface-tethered cationic peptides studies, reported that the immobilization of peptides to a surface should result in constraints on the peptide mobility and on the capacity of peptides to enter or even transpose the cellular membranes.…”
Section: Mode Of Antibacterial Actionmentioning
confidence: 99%
See 3 more Smart Citations